Role of the dopamine D5 receptor (DRD5) as a susceptibility gene for cervical dystonia. Issue 5 (1st May 2003) - Brancati, F; Valente, E M; Castori, M; Vanacore, N; Sessa, M; Galardi, G; Berardelli, A; Bentivoglio, A R; Defazio, G; Girlanda, P; Abbruzzese, G; Albanese, A; et al.
Abstract : Cervical dystonia (CD) is one of the most common forms of primary dystonia. The pathogenesis of the disease is still unknown, although evidence suggests a role for genetic factors. Recently, a polymorphism in the dopamine D5 receptor (DRD5) gene has been associated with the disease in a British population, suggesting that DRD5 is a susceptibility gene for CD. To confirm these data, we performed a case-control study of the microsatellite (CT/GT/GA)n at the DRD5 locus in 104 Italian CD patients and 104 healthy controls. The frequency of allele 4 was higher in the CD patients compared to the controls. This resulted in a twofold increased risk of developing the disease. These results provide further evidence of an association between DRD5 and cervical dystonia, supporting the involvement of the dopamine pathway in the pathogenesis of CD.